Analisis kebutuhan pengembangan lembar kerja anak pendidikan seksualitas anak usia dini terintegrasi dalam pembelajaran tematik terpadu - Dahlia Dahlia; Sutrisno Sutrisno; Alimatul Qibtiyah (AL-ASASIYYA: Journal Of Basic Education, 2020)
Referring to the rampant cases of child sexual violence, the care of all parties is needed. Therefore, it is necessary to take preventive measures to prevent cases of sexual violence against children. This preventive step is through sexuality education. Sexuality education has been integrated into integrated thematic learning, such as in the theme “Myself”, it is just that the material has not touched much on the actual problems faced by children. So, it is necessary to develop children's worksheets that contain sexuality education materials that children need. This study aims to analyze the need for sexuality education worksheets for children. This needs analysis includes an analysis of teachers' understanding of the concept of sexuality education and existing children's worksheets. Data obtained through interviews and documentation. The results showed that: (1) Teachers' understanding of the concept of sexuality education is still about identifying gender and introducing body parts that can be touched and cannot be touched by other people; and (2) The existing children's worksheets do not contain the sexuality education material that children need. Based on the results of the needs analysis, the authors recommend the development of integrated early childhood sexuality education worksheets in integrated thematic learning.